Cardiac output estimation based on arterial and venous blood gas analysis: proposal of a monitoring method - Santiago Giraldo Gutiérrez, David; José Velásquez Gutiérrez, Juan; Octavio Ruiz-Villa, Joaquín (Anestezjologia Intensywna Terapia, 2021)
Hemodynamic optimization is vital in high risk surgical patients or in high risk surgical procedures. The main objective of hemodynamic management is to maintain tissue perfusion and preserve aerobic metabolism through a cardiac output coupled with the metabolic demand. The technologies used for cardiac output monitoring use special techniques (e.g. lithium dilution or transpulmonary thermodilution) or implementation of dedicated devices with considerable rates of potential complications (pulmonary artery catheter). Thus, we propose a novel method to estimate cardiac output through the analysis of arteriovenous blood gases which could be an alternative to more expensive methods (minimally invasive devices, pulmonary artery catheter). A review of several formulas described in the literature to compute the variables needed to calculate cardiac output with the Fick principle was carried out. These formulas estimate the oxygen consumption using the O2 sensor integrated in the anesthesia workstation. The other variables in the Fick equation are derived from the arterial and venous blood gas analysis and parameters obtained from mechanical ventilators. By integrating the data gathered from the publications found, the authors created a comprehensive formula for calculation of cardiac output and the cardiac index using the parameters obtained from blood gas analysis. The presented method provides a more accessible and affordable way to monitor cardiac output in surgical high-risk patients in an environment with limited resources.